Design and implementation of fail -recover operation for embedded system based FPGA - M. Sabri, Salim; R. Badlishah, Ahmad, Prof. Madya Dr.; M. F., Melka (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.